Andersen's Code: Aristophanic Obscenity in Thumbelina - Bednarek, Bartłomiej (Classica et Mediaevalia, 2020)
In his seemingly innocent fairy tale Thumbelina, Hans Christian Andersen makes two allusions to Aristophanes. One of them is quite explicit, as the author makes a toad produce the sound co-ax, co-ax, brek-ek-eke-kex, which is a quotation from the Frogs. The other allusion is less conspicuous. In one of the first sentences of Thumbelina, an object that a woman needs in order to beget a child is referred to as a barleycorn. As I argue, even though on the surface it can be explained in terms of magic typical for fairy tales, it can be also understood as an obscene allusion to the sexual act. This results from the ambiguity, well-known in Andersen’s time, of the word κριθή, which in Aristophanes’ comedies can mean either barleycorn or penis.